Ab initio potential energy surface and anharmonic vibration spectrum of NF3 - Chen, Yan-Nan; Xu, Jian-Gang; Fan, Jiang-Peng; Ma, Shuang-Xiong; Guo, Tian; Zhang, Yun-Guang (Chinese physics B, 2024)
Potential energy surfaces (PESs), vibrational frequencies, and infrared spectra are calculated for NF 3 + using ab initio calculations, based on UCCSD(T)/cc-pVTZ combined with vibrational configuration interaction (VCI). Based on an iterative algorithm, the surfaces (SURF) program adds automatic points to the lattice representation of the potential function, the one-dimensional and two-dimensional PESs are calculated after reaching a convergence threshold, finally the smooth image of the potential energy surface is fitted. The PESs accurately account for the interaction between the different modes, with the mode q 6 symmetrical stretching vibrations having the greatest effect on the potential energy change of the whole system throughout the potential energy surface shift. The anharmonic frequencies are obtained when the VCI matrix is diagonalized. Fundamental frequencies, overtones, and combination bands of NF 3 + are calculated, which generate the degenerate phenomenon between their frequencies. Finally, the calculated anharmonic frequency is used to plot the infrared spectra. Modal antisymmetric stretching ν 5 and symmetric stretching ν 6 exhibit a phenomenon of large-intensity borrowing. This study can provide data to support the characterization in the laboratory.